PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN (ENDURANCE) PADA ATLET PUTRA BULUTANGKIS PB. ANGKASA PEKANBARU - anonim martila; zainur zainur; agus sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations that researchers have done with PB trainers. Space during training and during a match that looks less good endurance, this can be seen when athletes play long rally athletes often stall when playing, athletes often seem to lose power when they reach 3 sets, not free or not fast athletes move and move places, this is due to excessive fatigue so that the movement is not maximal, so that it can easily be defeated by the opponent. This research was carried out in PB PB. Angkasa Badminton Center jalan Angkasa No.02 Pekanbaru This research was conducted from June 2018 to March 2019. The design of this study was a one-group preetest-posttest design which was started by doing a Balke. After that the sample was given an Interval training program for 16 meetings to the athletes of PB Badminton boys. Angkasa Pekanbaru. After that, the Balke Posttest was done. The data obtained were analyzed descriptively, then the next research hypothesis was tested which had been proposed according to the problem, namely: "there is the influence of the Interval Training (X) exercise on endurance improvement (Y). Based on the analysis carried out, the value of the t count between the initial test and the final test of the Interval Training exercise on endurance with t table at a significant level of 0.05 with degrees of freedom N - 1 (8-1 = 7). This shows that the value of t arithmetic (9.75)> t table (1,895) thus it can be concluded that the hypothesis states that there is an effect of Interval Training (X) training on endurance (Y) on PB badminton male athletes. Angkasa Pekanbaru. Key Words: Interval training, endurance of badminton male athletes